An Experimental Investigation of Transpiration Cooling. Part I: Application of an Infrared Measurement Technique. (2003) - Wang, J. H.; Messner, J.; Stetter, H.
Abstract : This study was an investigation into the application of the infrared thermal imaging technique (IRTIT) to evaluate transpiration cooling performance through a porous wall. Two typical infrared thermograph systems, the AGA 782 short-wavelength system and the VARIOSCAN 3021 long-wavelength system, were employed to demonstrate the availability of the IRTIT measurement. In comparison with general infrared apparent temperature measurement, several factors that influence measurement accuracy need to be addressed in the application of the IRTIT in the region of transpiration cooling on the porous surfaces of turbine components. In this article, the influence of these factors on measurement accuracy is discussed, the corresponding calibration methods of the two infrared systems are described, and the ambient conditions and stability of the measurement are analyzed. Aporous circular tube was used as a specimen. The tube consisted of sintered chromium-nickel steel with a porosity of 21%. The experiment was carried out in the hotgas wind tunnel at the Institute of Thermal Turbomachinery at the University of Stuttgart, Stuttgart, Germany.